Microstructure evolution and performance effect of composite carbide (W,Ti)C enhanced Ni-based coatings fabricated by laser cladding - Yang Zhao; Wenqing Shi; Jiang Huang (Journal of Materials Research and Technology)
Composite carbides (W,Ti)C enhanced Ni-based coatings were fabricated by laser cladding on 316L stainless steel. The impact of composite carbides (W,Ti)C enhanced on Ni-based composite coatings' microstructure, wear and corrosion behavior are largely explored. The results show that the breaking down of composite phase (W,Ti)C speed up the production of MC and M23C6 and makes the distribution denser to improve wear-resisting properties. The particle sizes of W + TiC/Ni-based composite coatings are increasingly refined, and the crystal structure transitions from columnar dendrites, isometric, cellular, and eutectic to the eutectic organization. According to the results of friction and wear property tests, the friction coefficient and wear of W + TiC/Ni-based coatings gradually decreased with the increase of the mass fraction of W + TiC, and according to the friction and wear morphology. The generation of plastic deformation was hindered with MC and M23C6 composite carbides. Based on the results of electrochemical experiments, it can be seen that the corrosion resistance behaviour in sulfur-containing chloride environments gradually deteriorates as the mass fraction of W + TiC increases. In contrast, the corrosion resistance behaviour in chloride environments first deteriorates and then improves, suggesting that the corrosion resistance of MC and M23C6 composite carbides to sulfur-containing environments will deteriorate.